Flexible Perovskite Solar Cells: Progress and Prospects - Liang, Xiao; Ge, Chuangye; Fang, Qianru; Deng, Wanyuan; Dey, Sukumar; Lin, Haoran; Zhang, Yong; Zhang, Xintao; Zhu, Quanyao; Hu, Hanlin (Frontiers in Materials, 2021)
Flexible perovskite solar cells (PSCs) have shown great potential in the field of wearable power supply and integration with architectures in the future due to their advantages of high flexibility, light-weight, portability, and compatibility with irregular electronic products. As a promising photovoltaic technology compatible with roll-to-roll manufacture, flexible PSCs have made significant progress in the past several years through optimizing perovskite composition engineering, interface modification, fabrication process optimization, and exploitation of new charge transport materials. As a result, the champion light-to-electricity power conversion efficiency of flexible PSCs has exceeded 20% recently. In this mini review, the latest developments of flexible PSCs are systematically summarized and discussed, including the flexible substrates and electrodes, as well as high-quality perovskite thin film fabrication. Finally, a prospect on the massive-manufacturing of flexible PSCs as well as the challenges has been discussed.